Einleitung – Alemannische Dialektologie – Forschungsstand und Perspektiven - Pfeiffer, Martin; Streck, Tobias; Streckenbach, Andrea (Linguistik Online, 2019)
This special issue of Linguistik online presents contributions to the 19th Arbeitstagung zur alemannischen Dialektologie (Conference on Alemannic dialectology). This conference was not restricted to a single research theme, but aimed to reflect the whole range of topically and methodologically diverse research currently being carried out in the field of Alemannic dialectology. This introduction briefly summarizes each of the 19 contributions to the special issue, organized according to the sections “variation and change”, “dialect, space, and identity”, and “project reports”.